Exequias en Pamplona del Magisterio republicano: los orígenes del sistema educativo franquista - L´ópez Bausela, José Ramón (Huarte de San Juan. Geografía e Historia, 2006)
The Course of National Directions of celebrated Primary Education in Pamplona from the 1 to the 30 of June of 1938 represents full stop of the project developed by the republican Ministry of Public Instruction to form to the educational ones of a lay and proletarian school and constitutes, simultaneously, the first call that, with official character, the Ministry of National Education of incited to rebellion Spain organized to form catholic teachers, nationalist and forjadores of the new national school. Pamplona, surrounded in its aureole of nationalistic and religious mysticism, it was the chosen scene to temper the spirit of the trainees, but as much the Superior Meeting of Education of Navarra as their representatives were marginalized systematically in all the decisions of organizational and curricular character related to the Course.